Peningkatan Bobot Badan Dewasa Rusa Sambar melalui Seleksi di Penangkaran - B. Brahmantyo; nFN Wirdateti; T. Nugraha; A. Trasidiharta (Buletin Plasma Nutfah, 2011)
Selection on Adult Weight of Sambar Deer (Rusa unicolor). Deer are animals that has potential as producers of meat, through the exploitation of captive deer. Morphometric information and selection to improve the performance of Sambar deer has been done in Technical Implementation Unit of Animal Breeding and Artificial Insemination Institute, Village Api-api, District of Penajam Paser Utara, East Kalimantan. A number of 174 heads from a total population of Sambar deer recorded body weight, body length, width and chest circumference, length and width of head, also length and width of the ear. Results of selection of female and male based on body weight, were 52 females (60%, the intensity of selection 1:40) and six males (10%, the intensity of selection 1.74). Differential selection on males and females were 18.42 kg and 7.73 kg, respectively. Prediction of selection response of Sambar deer was 7845 kg with heritability estimation value (h2) was 0.60. AbstrakRusa merupakan satwa yang bepotensi sebagai penghasil daging. Melalui penangkaran eksploitasi, perburuan dapat dikontrol. Informasi morfometrik dan upaya seleksi untuk meningkatkan performan rusa Sambar telah dilakukan di UPTD Balai Pembibitan dan Inseminasi Buatan, Desa Api-api, Kab. Penajam Paser Utara, Kalimantan Timur. Sejumlah 174 data dari total populasi rusa Sambar dicatat bobot badan, panjang badan, lebar dan lingkar dada, panjang dan lebar kepala serta panjang dan lebar telinga. Berdasarkan seleksi induk dan jantan menurut bobot badan diperoleh 52 ekor induk (60%, intensitas seleksi 1,40) dan 6 ekor jantan (10%, intensitas seleksi 1,74). Diferensial seleksi pada jantan adalah 18,42 kg dan pada betina 7,73 kg, sehingga diperoleh respon seleksi dugaan rusa Sambar sebesar 7.845 kg dengan dugaan nilai h2 0,60.